(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): How do organizations achieve excellent results on an ongoing basis? Purpose: The purpose is to find out with what approach in the organization they achieve the permanent achievement of excellent results. What methods and approaches do they use for this. Method: A qualitative method was used for analysis. Review of literature from various Internet titles, articles, brochures, master’s theses. Results: In order to achieve permanently excellent results, it is necessary to include all employees, as well as all factors according to the EFQM model. Organization: The leadership of the organization and the related vision, values and strategy are especially important for the lasting achievement of lasting excellent results. Society: An An organization that permanently achieves excellent results must ensure that its operations do not harm the environment through their operations and are sustainable. Originality: Organizations follow the EFQM model, using the Radar tool to analyze data. Limitations/Future Research: The research could be extended to other building blocks and described for our organization.